PENGARUH STRUKTUR KEPEMILIKAN PADA KINERJA PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI PEMODERASI (studi pada perusahaan makanan dan minuman yang terdaftar di BEI) (Sekolah Tinggi Ilmu Ekonomi Atma Bhakti, 2011)
This research aims to find out the effect of ownership structure on the company performance with capital structure as moderating variable: a study on food and beverage companies listed in Indonesia Stock Exchange. The ownership structure in this research is categorized into managerial and external. Population used in this research is the companies operating in food and beverages that are listed in Indonesia Stock Exchange in 2005-2009. The sampling technique is purposive sampling, obtaining 85 companies sample in observation time. The data analysis instrument used is a multiple linear regression. This research shows that the Managerial and External Ownership Structure variables do not affect Company Performance variable. Meanwhile the moderating variable, capital structure, strengthens the effect between the managerial ownership structure and the company performance. The capital structure attenuates the effect between the external ownership structure and the company performance.